Exploring Men’s Experiences of Engagement With General Practice: A Qualitative Study - Ruth Mursa; Christopher Patterson; Gemma McErlean; Elizabeth Halcomb (Journal of Primary Care & Community Health)
Introduction: As males are less engaged with healthcare than females, they often present when a condition is more advanced, reducing the potential for early intervention. Little is known about why men are less engaged and what influences them to be more proactive. This study sought to explore men’s experiences of engagement with general practice. Methods: A qualitative descriptive study was nested within a sequential mixed-methods project. Semi-structured interviews were undertaken with 17 male staff and volunteers of the New South Wales Rural Fire Service about their experiences, attitudes, and preferences for general practice engagement. Thematic analysis was used to analyze data. Results: Five sub-themes emerged about men’s engagement with general practice. “Reasons for engagement” revealed motivations for seeking healthcare. “Seeking validation” explained how social influences impacted engagement. The “importance of relationships” highlighted the value men place on trust with the healthcare provider/team, and how this impacts engagement. “Interpersonal communication” addressed preferences for direct and authentic communication. Finally, “barriers to engagement” revealed the challenges in accessing care. Conclusions: Awareness of the barriers and facilitators to men’s engagement with general practice can inform strategies to improve care. This study suggests that health professionals play a crucial role in building therapeutic relationships with men and partnering with them in their healthcare journey to improve engagement and health outcomes.